Comparative Analysis of Left Ventricular Reverse Remodeling After Aortic Valve Replacement: Median Sternotomy, Minimally Invasive Approach, and TAVI - Telehuzova, Oleksandra V.; Yemets, Glib I.; Rudenko, Nadiya M. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To evaluate and compare the effectiveness of left ventricular reverse remodeling (LVRR) after three distinct types of aortic valve replacement (AVR): surgical aortic valve replacement via median sternotomy (SAVR), minimally invasive aortic valve replacement (MIAVR), and transcatheter aortic valve implantation (TAVI). Materials and Methods. This prospective observational study included 214 patients diagnosed with severe aortic stenosis who underwent valve replacement using one of the three approaches. Patients were allocated into groups based on the intervention method (TAVI: n=78, MIAVR: n=63, SAVR: n=73). A comprehensive evaluation of left ventricular morphology and function was performed using echocardiography at baseline, 1, 6, and 12 months post-intervention. Parameters assessed included left ventricular mass index (LVMI), volumes (LVEDV, LVESV), ejection fraction (LVEF), global longitudinal strain (GLS), and NT-proBNP levels. Functional capacity was evaluated using the NYHA classification. Results. All three methods contributed to LVRR, as evidenced by progressive reductions in LVMI and LV volumes, along with improvements in LVEF and GLS. The TAVI and MIAVR groups demonstrated earlier and more pronounced reverse remodeling, particularly during the first 6 months, while SAVR showed a more gradual yet steady improvement. NT-proBNP levels significantly decreased across all groups, reflecting improved hemodynamics. TAVI was associated with the most rapid early recovery, whereas MIAVR demonstrated the most balanced and sustained benefits over the 12-month follow-up. Conclusions. AVR, regardless of approach, promotes reverse remodeling of the left ventricle in patients with severe aortic stenosis. However, the rate and extent of remodeling vary by method. These findings highlight the need for an individualized approach in selecting the most appropriate valve replacement strategy, considering patient risk profiles, anatomical factors, and expected recovery trajectory.